2011
DOI: 10.1111/j.1524-4725.2011.01977.x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma Developing from an Epidermoid Cyst of the Ear

Abstract: The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The nature of the stimulus for malignant transformation in an epidermal cyst is uncertain [3]. It has been suggested that chronic irritation of the lesion could be a triggering factor [2].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The nature of the stimulus for malignant transformation in an epidermal cyst is uncertain [3]. It has been suggested that chronic irritation of the lesion could be a triggering factor [2].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that chronic irritation of the lesion could be a triggering factor [2]. Also there is growing evidence that human papillomavirus (HPV) infection may play a role in the development of nonmelanoma skin cancer [3, 4]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations